Effect of phosphorus biofertilizers and foliar spray of potassium fertilizers on growth and yield of sunflower (Helianthus annuus L.): Effect of phosphorus biofertilizers and foliar spray of potassium fertilizers on growth and yield of sunflower (Helianthus annuus L.) - B B PRAVEEN KUMAR; G SOMANAGOUDA (Journal of Oilseeds Research, 2020)
A field experiment was conducted during kharif to study the effect of phosphorus biofertilizers and foliar spray of potassium fertilizers along with RDF on sunflower. Application of 100% RDF along with soil application of VAM and foliar spray of 1% KNO3 at 45 DAS recorded significantly higher plant height, no. of green leaves/plant, leaf area, relative chlorophyll content, total dry matter production, seed yield (2019 kg/ha), stalk yield (3397 kg/ha) and harvest index (37%) followed by application of 75% RDF along with seed treatment of PSB at 20g/kg or soil application of 12 kg/ha VAM and foliar spray of 1% KNO3 at 45 DAS.